The mechanism of formation of the cutoff frequency in an acousto-optic delay line and some proposals for its measurement - Hasanov, Afig; Hasanov, Ruslan; Aghayev, Elgun; Ahmadov, Rovshan (Archives of Acoustics, 2026)
The structure of the acousto-optic delay line and possible areas of its application are discussed. The necessity of determining the cutoff frequency of the acousto-optic delay line in all areas of its application is substantiated. The relationship between the cutoff frequency of an electric circuit and its time constant is discussed. The obtained result is extrapolated to the acousto-optic delay line, in which the cutoff frequency is formed by a completely different mechanism. The mechanism of cutoff frequency formation in the acousto-optic delay line is discussed. It is shown that the cutoff frequency in the acousto-optic delay line is formed due to the finite velocity of interaction of the acoustic wave with the light beam in the photoelastic medium. Two methods for measuring the cutoff frequency of the acousto-optic delay line are discussed: the method of system-parametric measurement and the method of cursor measurement. The system-parametric method for measuring the cutoff frequency of the acousto-optic delay line is implemented based on the known values of the laser beam diameter and the velocity of propagation of the acoustic wave in the photoelastic medium. The cursor method for measuring the cutoff frequency of the acousto-optic delay line is implemented based on the parameters of the oscillogram of its response to the input action in the form of a rectangular pulse. Theoretical and experimental aspects of the application of these methods are discussed. Corresponding numerical examples and experimental results are given.